An analysis on the use of ethanol vapor as a disinfectant on aged piña-silk textile against Aspergillus niger - Sarmiento, Dale Carlo S.
Historical textiles are considered to be vulnerable to biodeterioration caused by fungal infestation in museum and heritage collections. While certain measures are done to prevent mold outbreaks in historical textiles, Aspergillus spp. can proliferate in typical museum environments (Bratu et al., 2009). This may pose a problem, especially in the UP CHE Costume Museum, where several piña dresses and objects are housed. Thus, there is a need to explore mold remediation methods on historical textiles made of piña. This study aims to determine the effectiveness of 30%, 70%, and 90% ethanol (EtOH) solution vapors in disinfecting aged piña-silk textiles against Aspergillus niger using fungicidal activity, tensile strength, color difference, and elongation as criteria; establishing the most effective concentration, afterwards. Piña-silk textile was artificially aged and divided into four hermetically-sealed chamber set-ups: B1 (control), B2 (30% EtOH), B3 (70% EtOH), B4 (90% EtOH). Corresponding EtOH concentrations were prepared and allowed to vaporize inside the chambers for 24 hours at room temperature. A series of AATCC and ASTM testing procedures were then done on the samples to quantify the criteria. The results suggest that B2 and B3 are effective disinfectants because they exhibited fungicidal activity and color changes that are within the industry standards, and non-significant differences (ɑ=0.05) in both the mean tensile strength and mean elongation. The concentration range of 30-70% EtOH vapors was implied to be effective. A 24-hour exposure to 30% EtOH vapors is the most effective disinfection method against A. niger, using aged piña-silk textile as matrix, considering lower fire risks (Lucas, Déniel, & Dantigny, 2017). Further research is recommended on the effectiveness of <30% EtOH vapors, and the use of other mold species.